Combination therapy of natural human interferon‐beta and ribavirin for chronic hepatitis C patients with injection drug use. Issue 10 (27th March 2013) - Morikawa, Hiroyasu; Kozuka, Ritsuzo; Fujii, Hideki; Iwai, Shuji; Enomoto, Masaru; Tamori, Akihiro; Saito, Shinobu; Kawada, Norifumi
Abstract : Aim: The aim of this study was to evaluate the efficacy and safety of combination therapy using natural human interferon‐β and ribavirin (IFN‐β/RBV) for chronic hepatitis C patients who were injection drug users (IDU) and resident in the Airin district of Osaka, containing the biggest slums in Japan. Methods: Twenty‐nine IDU with chronic hepatitis C received combination therapy of IFN‐β/RBV. The psychiatrist in charge evaluated the scores of the Zung Self‐rating Depression Scale (SDS), a self‐rating scale based on 20 questions. Univariate logistic regression analyses were used to determine the factors that significantly contributed to complete treatment and a sustained virological response (SVR). Results: Thirteen of the 29 patients achieved SVR according to the intention to treat analysis. All patients with a rapid virological response achieved SVR. No patient required a reduced dose of RBV because of a decrease in their hemoglobin level, or of IFN‐β because of a low level of white blood cells and platelet count. Two patients had psychological side‐effects and stopped the therapy early in the treatment; one patient had depression and the other had anxious depression. Univariate logistic regression analyses indicated that the stage of fibrosis was the only factor that contributed to SVR, and that the SDS test and past drug abuse contributed to completion of the treatment. Conclusion: IFN‐β/RBV combination therapy is useful for treating IDU.